2016
DOI: 10.1063/1.4939900
|View full text |Cite
|
Sign up to set email alerts
|

A gasdynamic gun driven by gaseous detonation

Abstract: Force tests were conducted at the long-duration-test shock tunnel JF12, which has been designed and built in the Institute of Mechanics, Chinese Academy of Sciences. The performance tests demonstrated that this facility is capable of reproducing a flow of dry air at Mach numbers from 5 to 9 at more than 100 ms test duration. Therefore, the traditional internal strain-gauge balance was considered for the force tests use in this large impulse facility. However, when the force tests are conducted in a shock tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…When the incident shock wave ruptures the second diaphragm, separating the driven section and nozzle, the shock wave is simultaneously reflected, which further compresses and stagnates the gas in the driven tube, thereby forming the high-temperature and highpressure gas in the nozzle inlet. As the diaphragm ruptures, a quasi-steady nozzle flow is established after the start transient [39].…”
Section: Experimental Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…When the incident shock wave ruptures the second diaphragm, separating the driven section and nozzle, the shock wave is simultaneously reflected, which further compresses and stagnates the gas in the driven tube, thereby forming the high-temperature and highpressure gas in the nozzle inlet. As the diaphragm ruptures, a quasi-steady nozzle flow is established after the start transient [39].…”
Section: Experimental Facilitymentioning
confidence: 99%
“…When the incident shock wave ruptures the second diaphragm, separating the driven section and nozzle, the shock wave is simultaneously reflected, which further compresses and stagnates the gas in the driven tube, thereby forming the high-temperature and high-pressure gas in the nozzle inlet. As the diaphragm ruptures, a quasi-steady nozzle flow is established after the start transient [39]. In order to study the impacts of the starting waves on the test data, and to verify the accuracy of the program, the experiment uses the half-sphere with a radius of 20 mm to measure the heat flux at the stagnation point and nearby, and uses the pitot rod to measure the pressure at the stagnation point.…”
Section: Experimental Facilitymentioning
confidence: 99%
“…Subsequently, a single-stage gas gun driven by gaseous detonation was developed by Batchelor; the gas gun achieved velocities exceeding 3 km/s [22]. Li [23] discussed the internal ballistic process of a single-stage gas gun and verified its practical feasibility through experiments. Li also estimated the driving capability of a detonation driver for a two-stage light gas gun by solving the quasi-one-dimensional Euler equations; it was found that the detonation driver was sufficient to obtain projectile velocities of up to 8 km/s in a two-stage light gas gun.…”
Section: Introductionmentioning
confidence: 99%